Efeito do condicionamento de inlays cerâmicas com diferentes concentrações de ácido fluorídrico na carga de fratura sob fadiga de pré-molares restaurados - Missau, Taiane Secretti (2016)
The aim of this study was to evaluate the effect of different concentrations of hydrofluoric acid on the fatigue failure load of premolars restored with feldspathic ceramic inlays. Sixty upper premolars were embedded in PVC cylinders with acrylic resin up to 2 mm below the cement- enamel junction and prepared using an adapted device for that purpose. Teeth were randomly divided into three groups (n=20): HF1, HF5, and HF10, (conditioning with hydrofluoric acid for 60 s at concentrations of 1%, 5%, and 10%, respectively). Preparations were scanned using the CAD/CAM system with prefabricated blocks of feldspathic ceramic. The internal surfaces of the inlays were treated according to the groups, followed by application of silane coupling agent, and RelyX ARC resin cement was applied for cementation. The fatigue failure load was determined using the staircase method (10 Hz and 105 cycles in each step). The initial load (585.5 N) was applied on the slopes of the cusps through a cylinder attached to the test machine (InstronElectroPuls E3000). The fractured teeth were analyzed under a stereomicroscope for failure analysis. Statistical analysis was performed using one-way ANOVA. There was no statistical difference among the fatigue failure load of the tested groups: HF1 (448.5 N ±79.1), HF5 (360.7 N ±55.4), and HF10 (409.5 N ±121.1). Regarding the fracture mode, there was a predominance of interface fracture (50%), followed by cusp fracture (34.6%). It can be concluded that hydrofluoric acid concentrations used (1%, 5%, and 10%) did not influence the fatigue failure load of feldspathic ceramic inlays cemented on premolars.